PENDAPAT IMAM MÂLIK BIN ANAS TENTANG KHULU‘ DAN RELEVANSINYA DENGAN HUKUM PERKAWINAN DI INDONESIA - Ahmad Hoyir (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2014)
In the discussion of khulu‘, Imam Mâlik bin Anas argued that khulu‘ and thalaq are similar. This understanding is caused by a difference of opinions among the scholars. In this case, the verdict delivered by the Bandung Islamic Court in Case Number: 2878/ Pdt.G/2010/PA.Bdg has compatibility with the opinion of Imam Mâlik. In its verdict, the court of Religious Bandung was likening khul'u and thalaq, and set it as thalaq ba‘in, so the iddah which fell on women in khulu‘ is three times qurû’', and women have to return the part of dowries to the husband. This paper attempts to explain khulu‘ according to Imam Mâlik and compliance with laws and regulations.